2008
DOI: 10.1111/j.1745-7254.2008.00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of higenamine in Radix AconitiLateralis Preparataas a beta2-adrenergic receptor agonist1

Abstract: Aim: To screen beta2-adrenergic receptor (β 2 -AR) agonists from Radix Aconiti Lateralis Preparata (RALP) as potential drug leads for asthma using a sensitive cell-based agonist assay. Methods: The β 2 -AR gene was stably expressed by Chinese hamster ovary (CHO) cells also stably expressing a cyclic adenosine monophosphate (AMP) response element-linked enhanced green fluorescent protein reporter gene. The cells were used to screen agonists from high-performance liquid chromatographic fractions of an extract of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 17 publications
3
47
0
Order By: Relevance
“…So considering this phenomenon, it is suggested that b-adrenoceptors activated by higenamine increased the cAMP. 6,7 We do not have any data regarding the results of this study that higenamine has some PDE5 inhibitor activity. We guess that action mechanisms of higenamine and PDE-5 inhibitor showed synergistic effect have two signal pathways.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…So considering this phenomenon, it is suggested that b-adrenoceptors activated by higenamine increased the cAMP. 6,7 We do not have any data regarding the results of this study that higenamine has some PDE5 inhibitor activity. We guess that action mechanisms of higenamine and PDE-5 inhibitor showed synergistic effect have two signal pathways.…”
Section: Discussionmentioning
confidence: 77%
“…Higenamine mediates cardiotonic, 5,6 vascular relaxation, 7 bronchodilator 8 and anti-thrombotic effects, 9,10 and reduces apoptotic cell death in vivo, 11 suggesting that higenamine has various actions on the cardiovascular system and that it may have an effect on penile erection.…”
Section: Introductionmentioning
confidence: 99%
“…During the experiment, animals were manipulated as previously described [12] . Briefly, the animals were placed in an inhalation cage, and each animal was exposed to atomized 0.1% histamine solutions for 20 s at the rate of 0.8 mL/min.…”
Section: Transient Transfection and Luciferase Assaymentioning
confidence: 99%
“…Briefly, this cell line The isolated guinea pig tracheal strips relaxation model Hartley strain guinea pigs were sacrificed with an overdose of pentobarbital (75 mg/kg, ip). Tracheal strips were removed and manipulated as previously described [12] . Acetylcholine (ACh) was added to the organ bath to induce the contraction of smooth muscle.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation